Effect of Roughage Source on the Composition and Colonization of Rumen Bacteria and Methanogens in Dumont and Mongolian Sheep - Wenliang Guo; Hongyang Liu; Yue Wang; Meila Na; Ran Zhang; Renhua Na (Animals)
Understanding the influence of the sheep breed and roughage source on the composition of rumen bacteria and methanogens is essential for optimizing roughage efficiency. The experiment employed a 2 × 2 factorial design. Twenty-four Dumont and Mongolian sheep (initial body weight of 18.94 ± 1.01 kg) were randomly assigned by breed to two dietary treatment groups (AH: alfalfa hay; CS: corn straw); the experiment lasted 90 days. The results showed that sheep fed alfalfa hay diets had a higher feed intake and weight gain, and Dumont sheep had a higher feed intake than Mongolian sheep (p < 0.05). The diversity and composition of ruminal bacteria and methanogens differed between Dumont and Mongolian sheep fed either AH or CS diets. The taxonomic analysis revealed a distinct clustering pattern based on the roughage source, but not on the breed. When fed a corn straw diet, the bacterial Chao1 index of Dumont sheep increased (p < 0.05), while the diversity and richness of methanogens in Mongolian sheep increased (p < 0.05). Additionally, we have identified unique biomarkers for the rumen bacteria and methanogens of Dumont and Mongolian sheep in response to different roughage sources. The results suggest that the differences in the microbiota of the sheep were associated with the roughage source and breed. The higher growth performance of Dumont sheep might be attributed to the increase in bacterial diversity and the decrease in methanogenic bacteria diversity.